2007
DOI: 10.4161/cbt.6.9.4541
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and clinical studies with the multi-kinase inhibitor CEP-701 as treatment for prostate cancer demonstrate the inadequacy of PSA response as a primary endpoint

Abstract: Purpose-CEP-701 is a potent inhibitor of trk receptors that causes cell death in prostate cancer (PC) models. CEP-701 binds to serum proteins and a preprostatectomy study was performed to assess prostate tissue penetration and clinical response to CEP-701.Methods-Growth assays and Western blot analyses were performed to evaluate CEP-701 kinase inhibition. In a preprostatectomy study, patients received CEP-701 for five days prior to prostatectomy and prostate tissue analyzed for CEP-701 levels. A phase II dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…While the Trk blocker, CEP-701, has been investigated in clinical trials for the treatment of prostate and pancreatic cancer, the results have yet to show promise. An obstacle for the use of CEP-701 is its ability to bind to serum proteins, thereby limiting the amount of free drug for tumor penetration, as well as the limited ability of the drug to penetrate a tumor [31]. Therefore, new Trk blockers are needed as alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…While the Trk blocker, CEP-701, has been investigated in clinical trials for the treatment of prostate and pancreatic cancer, the results have yet to show promise. An obstacle for the use of CEP-701 is its ability to bind to serum proteins, thereby limiting the amount of free drug for tumor penetration, as well as the limited ability of the drug to penetrate a tumor [31]. Therefore, new Trk blockers are needed as alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Agus et al [32] demonstrated that pertuzumab alone may have clinical utility in castration-resistant PCa after progression from taxane-based therapy has been performed. In addition Collins et al [40] started a clinical study to evaluate the effects of CEP-701 in PCa patients with hormone refractory disease. The authors concluded that the evaluation of PSA response was an inadequate indicator of response in CEP-701 treated PC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that lestaurtinib can suppress androgen-inducible gene expression is another supporting evidence that lestaurtinib can potentially be used in androgen-sensitive prostate cancer. Although previously lestaurtinib failed in a clinical study of androgen-refractory prostate cancer [17], the reason for the failure could be due to selection of a wrong population of prostate cancer. Figure 2 showed the resistance of PC3 and DU145 cells, two androgen-independent prostate cancer cell lines, and supported this possibility.…”
Section: Discussionmentioning
confidence: 99%